To solve the inequality \( 121x^2 - x^4 \geq 0 \), let's first rewrite the expression:
\[ -x^4 + 121x^2 \geq 0 \]
To make it easier to factor, let's rearrange it:
\[ 121x^2 - x^4 \geq 0 \]
Next, we can factor out \( x^2 \):
\[ x^2(121 - x^2) \geq 0 \]
Now, we can set each factor equal to zero to find the critical points:
- \( x^2 = 0 \) gives \( x = 0 \).
- \( 121 - x^2 = 0 \) gives \( x^2 = 121 \), hence \( x = \pm 11 \).
So the critical points are \( x = -11, 0, 11 \).
Next, we will use these points to test the intervals around them to determine where the product is non-negative. The intervals are:
- \( (-\infty, -11) \)
- \( (-11, 0) \)
- \( (0, 11) \)
- \( (11, \infty) \)
Testing the intervals:
-
For the interval \((- \infty, -11)\), choose \( x = -12 \): \[ (-12)^2(121 - (-12)^2) = 144(121 - 144) = 144(-23) < 0 \] This interval does not satisfy the inequality.
-
For the interval \((-11, 0)\), choose \( x = -1 \): \[ (-1)^2(121 - (-1)^2) = 1(121 - 1) = 1(120) > 0 \] This interval satisfies the inequality.
-
For the interval \( (0, 11)\), choose \( x = 1 \): \[ (1)^2(121 - (1)^2) = 1(121 - 1) = 1(120) > 0 \] This interval satisfies the inequality.
-
For the interval \( (11, \infty)\), choose \( x = 12 \): \[ (12)^2(121 - (12)^2) = 144(121 - 144) = 144(-23) < 0 \] This interval does not satisfy the inequality.
Endpoints:
-
At \( x = -11 \): \[ (-11)^2(121 - (-11)^2) = 121(0) = 0 \] This satisfies the inequality.
-
At \( x = 0 \): \[ (0)^2(121 - (0)^2) = 0(121) = 0 \] This satisfies the inequality.
-
At \( x = 11 \): \[ (11)^2(121 - (11)^2) = 121(0) = 0 \] This satisfies the inequality.
Final solution:
The intervals satisfying the inequality are:
\[ [-11, 0] \cup [0, 11] \]
Since the point at \( x=0 \) is included in both intervals, we can simplify this to:
\[ [-11, 11] \]
The answer is:
Part B: The solutions are the values of \( x \) in the interval \([-11, 11]\).